Influence of adjuvant therapies on organ-specific recurrence of cutaneous melanoma: A multicenter study on 1383 patients of the prospective DeCOG registry ADOReg - Wohlfeil, Sebastian A.; Kranzmann, Leonie; Weiß, Christel; von Wasielewski, Imke; Klespe, Kai C.; Kähler, Katharina C.; Weichenthal, Michael; Schadendorf, Dirk; Zimmer, Lisa; Mohr, Peter; Meier, Friedegund; Pfoehler, Claudia; et al. (International Journal of Cancer, 2024)
This study investigated whether adjuvant treatments in stage III cutaneous melanoma (CM) influenced patterns of recurrence. Patients with primary (n = 1033) or relapsed CM (n = 350) who received adjuvant therapies with Nivolumab (N), Pembrolizumab (P), or Dabrafenib and Trametinib (D + T) were extracted from the prospective multicenter real-world skin cancer registry ADOReg. Endpoints were progression-free survival (PFS), distant metastasis-free survival (DMFS), organ-specific DMFS, and overall survival (OS). For primary cases, D + T indicated an improved PFS (1- and 2-year PFS: 90.9%; 82.7%) as compared to P (81.0%, 73.9%; p =.0208), or N (83.8%, 75.2%; p =.0539). BRAF-mutated(mut) CM demonstrated significantly lower PFS (p =.0022) and decreased DMFS (p =.0580) when treated with immune checkpoint inhibitor (ICI) instead of D + T. Besides, NRAS-mut CM tended to perform worse than wt CM upon ICI (PFS: p =.1349; DMFS: p =.0540). OS was similar between the groups. Relapsed cases showed decreased PFS, DMFS, and OS in comparison to primary (all: p <.001), without significant differences between the subgroups. Organ-specific DMFS was significantly altered for primary cases with bone (p =.0367) or brain metastases (p =.0202). In relapsed CM, the frequency of liver (D + T: 1.5%; P: 12%; N: 9%) and LN metastases (D + T: 1.5%; P: 12%; N: 10.2%) was significantly lower with adjuvant D + T than ICI. NRAS-mut CM showed increased recurrence in primary and relapsed cases. These data show that adjuvant D + T is superior to ICI in primary BRAF-mut CM.
CRIS-Team Scopus Importer:2024-07-19
Keywords: adjuvant treatment; immune checkpoint inhibition; melanoma; targeted therapy; therapy resistance